Construct validity, floor and ceiling effects, data completeness and magnitude of change for the eight-item HAKIR questionnaire: a patient-reported outcome in the Swedish National Healthcare Quality Registry for hand surgery. (March 2021) - Carlsson, Ingela K; Ekstrand, Elisabeth; Åström, Mikael; Stihl, Kerstin; Arner, Marianne
Introduction: The aim of this study was to evaluate the construct validity, floor and ceiling effects, data completeness and magnitude of change over time for the eight-item patient questionnaire (HQ-8) in the Swedish Healthcare Quality Registry for hand surgery (HAKIR). Methods: Construct validity was investigated through predefined hypotheses and correlation statistics between the single items in HQ-8 (pain on load, pain on motion without load, pain at rest, stiffness, weakness, numbness, cold sensitivity and ability to perform daily activities) and QuickDASH. Floor and ceiling effects and data completeness were analysed at preoperative ( n  = 13, 197), three months ( n = 10, 702) and one year ( n  = 9, 986) responses from hand surgery patients. Effect sizes were calculated for pre- and postoperative change scores in elective conditions and postoperative scores for acute conditions. Results: Correlation coefficients at pre, 3 and 12 months ranged from 0.44 to 0.79 in the total group. No ceiling effect occurred, but a floor effect for the total group was noted for all items at all follow-ups. Missing responses were < 2.6% except for cold sensitivity. The effect sizes varied from small to large for individual items in elective diagnoses. For acute injuries, small effect sizes were found. Discussion: This study provides evidence of construct validity of HQ-8, lack of ceiling effect, expected floor effect, good data completeness and an ability to detect changes over time. The results indicate that HQ-8 measures unique aspects of disability. The HQ-8 could complement the Quick-DASH in describing patient-reported outcomes after hand surgery.